Plasma total homocysteine level in mothers of children with clubfoot - Karakurt, L; Yilmaz, E; Serin, E; Bektas, B; Çikim, G; Gürsu, F (Lippincott Williams & Wilkins, 2003)
The pathogenesis of clubfoot is unknown despite numerous hypotheses. To clarify the relationship between the plasma total homocysteine level and congenital idiopathic clubfoot, blood samples from mothers of children with congenital idiopathic clubfoot (group 1) and mothers of children without congenital anomaly (group 2) were studied. Groups were the same for factors affecting the plasma total homocysteine level. Mean plasma total homocysteine level was 16.34 +/- 4.78 mumol/L in group I and 11.02 +/- 1.85 mumol/L in group 2, and there was significant statistical difference between the groups (P < 0.05). Congenital idiopathic clubfoot showed a significant association with high plasma total homocysteine level. This study may be a step toward clarification of clubfoot pathogenesis.
Keywords: plasma total homocysteine level; congenital idiopathic clubfoot; pathogenesis